x+y=3 y=3-2x so x+3-2x=3 so x=0 0+y=3 so y=3
0
0.5
If you mean: x+y = 7 and x-y = 2 then x = 3 and y = 4
If x = 3 and y = 4 then the answer is 2
X = 17.7 + 0.1y
y
m
2/y + 1 + 3 + 5y
33/4
x+y+z/3 (x plus y plus z divided by 3)
Oh, dude, you're hitting me with some math here. So, like, you've got 4 x's and 3 y's, right? So, you can simplify that expression as 4x + 3y. It's like organizing a messy room, but with letters and numbers.
the Y in the sentence X plus Y equals 5 is Y=3 or 2 if the X is 2 or 3
Y = x - 7
y = 2
The average is the sum of variables divided by their count. For an instance:x = 6y = 102z = 9The average will be( 6 + 102 + 9 ) / 3 = 117 / 3 = 39
It is: (-10)+(-3)+4 = -9